(untitled) - Meuser, Helmut (New York, 2013)
This book provides a comprehensive overview of remediation and rehabilitation techniques and strategies for contaminated and anthropogenically disturbed land. Rehabilitation approaches in the urban environment, such as brownfield redevelopment and urban mining, are discussed. In relation to contaminated land, techniques for soil containment and decontamination of soil, soil vapour and groundwater are comprehensively and systematically presented. Complicated treatment techniques are schematically depicted and can be readily understood. Agricultural, silvicultural and environmentally sustainable rehabilitation strategies for reclaiming disturbed land/terrain in former mining or natural-resource extraction areas, such as open-cast mines, quarries, harvested peatlands, and subsided mining terrain (sinkholes), are introduced. This book will be a useful tool for students, researchers, private consultants and public authorities engaged in the treatment of contaminated or disturbed land.
Ô nhiễm đất và Kỹ thuật phục hồi
Keywords: Soil remediation,Phục hồi đất